The initial “ictus” of a symphony orchestra at the Atlantic headquarters, University of Costa Rica - Zamora-Ulate, Mauricio (2021)
A study was conducted to analyze the knowledge and organizational elements were analyzed in the conformation and sustainability of the Atlantic Symphony Orchestra. This autoethnography used personal memory, self-observation, self-reflection, interviews, and the systematization of experiences as a tool to collect information from the protagonists of the initial story, which was analyzed and presented in this work. Thus, it was obtained a musician profile, which is the importance of the group's relationship with other organizations and the relevance that an orchestra presentation can have for its development.